Being appropriately professional: the interaction between professionalism, ICT and knowledge transfer. (July 2016) - Butler, Clare
Abstract : This article examines how professionalism impacts on the interaction and knowledge transfer of professionals within open plan workspaces and between distributed workplaces when using ICT. Knowledge is key to the system of professions and the power of professionals. At the same time, professional work requires professionals to behave in an appropriate and professional‐like manner, and this includes sharing knowledge with colleagues. Yet, the ideology of professionalism is changing. Alongside, professionals are working differently, including across distributed workplaces and often interacting via ICT. These shifting contexts make understanding the interaction between professionalism, knowledge transfer and ICT crucial. Drawing on Goffman's work, particularly his exposition of interaction rituals, interviews with accountants reveal that when using ICT, the professional framework of interaction – what can be said, who has the right to speak and who is the audience – meets appropriateness in sometimes contradictory ways, potentially limiting the growth and propagation of knowledge.